2023
DOI: 10.3389/fcvm.2023.1135127
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs as biomarkers of risk of major adverse cardiovascular events in atrial fibrillation

Abstract: Atrial fibrillation is a complex and multifactorial disease. Although prophylactic anticoagulation has great benefits in avoiding comorbidities, adverse cardiovascular events still occur and thus in recent decades, many resources have been invested in the identification of useful markers in the prevention of the risk of MACE in these patients. As such, microRNAs, that are small non-coding RNAs whose function is to regulate gene expression post-transcriptionally, have a relevant role in the development of MACE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Thus, they might be useful molecular markers for monitoring for pregnancy-associated cardiovascular diseases, opening new possibilities for early, non-invasive prenatal diagnosis and thus prevention, as recently reviewed by Omran et al [199]. The identification of microRNAs as suitable biomarkers has also been extensively reported in major adverse cardiovascular events in atrial fibrillation [200], heart failure [201] and arrhythmogenic cardiomyopathies [202], among other cardiovascular diseases. Importantly, their use in prevention, treatment, and management is progressively emerging, although some additional efforts are required before they fully enter the clinical arena, such as, for example, providing adequate standardization for the methodology of purifying and detecting microRNA [200].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, they might be useful molecular markers for monitoring for pregnancy-associated cardiovascular diseases, opening new possibilities for early, non-invasive prenatal diagnosis and thus prevention, as recently reviewed by Omran et al [199]. The identification of microRNAs as suitable biomarkers has also been extensively reported in major adverse cardiovascular events in atrial fibrillation [200], heart failure [201] and arrhythmogenic cardiomyopathies [202], among other cardiovascular diseases. Importantly, their use in prevention, treatment, and management is progressively emerging, although some additional efforts are required before they fully enter the clinical arena, such as, for example, providing adequate standardization for the methodology of purifying and detecting microRNA [200].…”
Section: Discussionmentioning
confidence: 98%
“…The identification of microRNAs as suitable biomarkers has also been extensively reported in major adverse cardiovascular events in atrial fibrillation [200], heart failure [201] and arrhythmogenic cardiomyopathies [202], among other cardiovascular diseases. Importantly, their use in prevention, treatment, and management is progressively emerging, although some additional efforts are required before they fully enter the clinical arena, such as, for example, providing adequate standardization for the methodology of purifying and detecting microRNA [200]. Nonetheless, the path to use microRNAs for the treatment of cardiovascular diseases is promising as clinical trials in other disease contexts have also been successful [203] and the first approaches are already in the way for heart failure [204].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA can also play an important role as predictors of coronary vascular disease in patients with AF. A study conducted by Reyes-Garcia et al showed that patients with highly increased risks of a major adverse cardiovascular event had significantly higher levels of miR-22-3p and miR-107 and lower levels of miR-146a-5p [24]. miRNA also have an important role in vascular health and atherosclerotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although miRNAs may appear as attractive, new biomarkers for predicting AFmonitoring AF treatment effects, predicting major adverse events in AF patients, or characterizing the underlying mechanism of the development and progression of AF [26,27,[30][31][32][33][34]43]-there are several factors currently limiting their use in daily clinical practice. A major problem is the lack of standardization of the miRNA analysis process, from obtaining the RNA over the purification of the material to the measurement including the normalization of the measured miRNA levels, which has impact on the results and makes them difficult to compare [26,27,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%